Transient transformation of artemisinic aldehyde ∆ 11 (13) double bond reductase (dbr2) gene into Artemisia annua L. - Elfahmi Elfahmi; Fany Mutia Cahyani; Andre Ditya Maulana Lubis; Tati Kristanti; Sony Suhandono (Universitas Gadjah Mada, 2016)
Global demand of antimalarial drug artemisinin has a gap with production capacity from existing sources since the low content of this compound from Artemia annua L. Genetic engineering-based strategy for A. annua plant on key enzymes in artemisinin biosynthetic pathway is needed. Artemisinic aldehyde ∆ 11 (13) double bond reductase (dbr2) is one of the key enzyme on artemisinin biosynthesis which was studied in this research. Agrobacterium tumefaciens-mediated transformation of A. annua using dbr2 was carried out. Synthetic dbr2 was ligated into pCAMBIA1303 and transformed into Escherichia coli DH5α. pCAMBIA1303-dbr2 plasmid was transformed to A. tumefaciens AGL1. Leaves of A. annua were infected by positive transformant of recombinant A. tumefaciens (OD600 ≈ 1) supplemented with acetosyringone 50 ppm, and Silwet S-408 0.02%. Samples were incubated in desiccators connected with vacuum pump, this method is called infiltration vacuum. Leaves were covered in dark for 45 min, and co-cultivated on MS co-cultivation media for 3 days. All leaves were washed in 300 ppm cefotaxime and divided into 2 parts; 3 leaves for GUS histochemical assay and 300 mg of leaves for HPLC analysis. Transient transformation was done in triplicate. In GUS histochemical assay, pCAMBIA1303 and pCAMBIA-dbr2 showed positive blue spot where coefficient of variance was less than 5%. PCR analysis for genomic DNA of transformed A. annua showed a positive result of inserted dbr2 recombinant indicated by migration profile and direct sequencing analysis. It could be concluded that pCAMBIA-dbr2 construct and transformation into A. annua have been successfully performed.